Identifying Undergraduate Students’ Misconceptions in Understanding Acid Base Materials (Jurnal Pendidikan IPA Indonesia, 2020)
Students’ misconceptions have become phenomenon in teaching and learning, especially in chemistry which is considered as difficult subject. The objective of this study is to identify undergraduate student’s misconception profiles related to acid-base concepts in inorganic chemistry. This test was conducted with 15 item three tier multiple choices test. Data were identified descriptively and qualitatively. This test instruments are judged as valid with CVR score of 0,99 and mean of 1,73. Meanwhile, the reliability for this instrument varies for each tier combination; for tier one only, r11 was given reliability score for 0,93; for combination tier one and tier two, r11 score was 0,90, and for combination of all tiers, r11 score was 0,81. The test conducted revealed that average percentage of misconception in this test is 33.31% for all items. The highest misconception profile is 60,61% in item no.6 hard soft acid base concept. This includes 15,15% misconception false positive, 9,09% misconception false negative, and 36.36% specific misconception.